Ayudenmen A Sacar EL Resultado De Los Productosss
(x²+3x-2)x²
xy(x²-xy+y²)x
-x²y³(4-3xy²+2x²y³)
1/3x³(6-3x³y+9x²y³(
(2x³).(5x³)
2(12x³).(4x)
35.(2x²y³z)
4(5x²y³z).(2y²z²)
(18x3³y²Z⁵).(6x³yz)
(-2x³).(-5x).(-3x²)
2xⁿ(xⁿ-2xⁿ⁺¹)
Respuestas
Respuesta dada por:
3
(x²+3x-2)x² = ![x^{4}+3 x^{3} -2 x^{2} x^{4}+3 x^{3} -2 x^{2}](https://tex.z-dn.net/?f=+x%5E%7B4%7D%2B3+x%5E%7B3%7D+-2+x%5E%7B2%7D++)
xy(x²-xy+y²)x =![x^{4}y - x^{3}y+ x^{2} y^{2} x^{4}y - x^{3}y+ x^{2} y^{2}](https://tex.z-dn.net/?f=+x%5E%7B4%7Dy+-++x%5E%7B3%7Dy%2B+x%5E%7B2%7D++y%5E%7B2%7D+++)
-x²y³(4-3xy²+2x²y³) =![-4 x^{2} y^{3} + 3 x^{3} y^{5}-2 x^{4} y^{6} } -4 x^{2} y^{3} + 3 x^{3} y^{5}-2 x^{4} y^{6} }](https://tex.z-dn.net/?f=-4+x%5E%7B2%7D++y%5E%7B3%7D+%2B+3+x%5E%7B3%7D+y%5E%7B5%7D-2+x%5E%7B4%7D+y%5E%7B6%7D++%7D+++)
(2x³).(5x³)=![10 x^{6} 10 x^{6}](https://tex.z-dn.net/?f=10+x%5E%7B6%7D+)
2(12x³).(4x)=![96 x^{4} 96 x^{4}](https://tex.z-dn.net/?f=96+x%5E%7B4%7D+)
35.(2x²y³z) =![70 x^{2} y^{3} z 70 x^{2} y^{3} z](https://tex.z-dn.net/?f=70+x%5E%7B2%7D++y%5E%7B3%7D+z+)
4(5x²y³z).(2y²z²) =
xy(x²-xy+y²)x =
-x²y³(4-3xy²+2x²y³) =
(2x³).(5x³)=
2(12x³).(4x)=
35.(2x²y³z) =
4(5x²y³z).(2y²z²) =
Respuesta dada por:
0
Respuesta:
Explicación paso a paso:
lo siento es 1x4z43y
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 10 años
hace 10 años
hace 10 años